Balloon Dilation in Sporadic Inclusion Body Myositis Patients with Dysphagia - Ken-ya Murata; Ken Kouda; Fumihiro Tajima; Tomoyoshi Kondo (Clinical Medicine Insights: Case Reports, 2013)
Here, we describe balloon catheter dilation at the upper esophageal sphincter (UES) in three sporadic inclusion body myositis (s-IBM) patients with dysphagia. Initially, we performed IVIg therapy, and, three months later, switched to balloon dilation therapy. A 12-Fr balloon catheter was inserted from the mouth under fluoroscopy and the balloon inflated at the UES. The catheter was pulled back and re-inserted several times. We examined videofluoroscopy (VF) and pressure at the oropharynx, hypopharynx and UES using computed pharyngoesophageal manometry (CPM). Before both therapies, the VF study revealed a very small amount of barium paste passing through the UES. After balloon dilation therapy, as well as IVIg, subjective complaints of dysphagia disappeared and the VF study revealed an increased amount of barium paste passing through the UES. We conclude that balloon dilation therapy is a complementary method for conventional dysphagia therapies in s-IBM patients with dysphagia.